Dampak Mitigasi Bencana Terhadap Pertumbuhan Pariwisata Di Daerah Kepulauan - Lasaiba, Mohammad Amin (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2024)
As the world's largest archipelago, Indonesia is vulnerable to various natural disasters such as earthquakes, tsunamis, volcanic eruptions, and floods. These conditions pose significant challenges to the tourism sector, one of the main contributors to the national economy. This study explores the impact of disaster mitigation on tourism growth in Indonesia's island regions. A literature review method was used to collect and analyze data from various relevant sources, including scientific journals, books, research reports, and media articles. The research findings indicate that effective disaster mitigation measures, such as the development of resilient infrastructure, comprehensive risk planning and management, community education and preparedness, and the use of modern technology for early warning systems, can reduce the negative impact of disasters and accelerate the recovery of the tourism sector. Additionally, cooperation between the government, private industry, and communities plays a crucial role in the success of mitigation efforts. With comprehensive and collaborative mitigation measures, Indonesia can enhance the competitiveness of its tourist destinations, strengthen tourist confidence, and support the national economy. The study concludes that disaster mitigation must be integral to tourism development policies to ensure safe and sustainable destinations.